Violence as a Form of Oppression towards Black Women in Octavia E Butler’s Kindred - Hasanady, Qatrunnada Viranda; Handayani, Rika (Puitika, 2024)
This article analyzes oppression of black women in Octavia E Butler’s novel entitled Kindred. The primary source is the novel Kindred by Octavia Butler while the secondary sources used are books and articles.The aim of this research to identify the oppression experienced by the black women represented by the black female characters in Kindred. In revealing the issue of oppression of the black women, the writers refer to Black Feminism Theory proposed by Patricia Hill Collins . The result of the study shows that the black women experience the regulation of black women’s bodies as the form of oppression. In this sense, black women face physical violence that leads to psychological violence. Furthermore, the other body regulation is rape.The study also shows that both white men and white women can be the perpetrators of the oppression towards black women.